Magnetoacoustic waves in a highly magnetostrictive Fe72Ga28 thin film - Marc Rovirola; M. Waqas Khaliq; Blai Casals; Adrian Begué; Neven Biskup; Noelia Coton; Joan Manel Hernàndez; Miguel Angel Niño; Michael Foerster; Alberto Hernández-Mínguez; Rocío Ranchal; Marius V. Costache; et al. (APL Materials)
The interaction between surface acoustic waves and magnetization offers an efficient route for electrically controlling magnetic states. Here, we demonstrate the excitation of magnetoacoustic waves in galfenol thin films with a 28 at. % gallium composition, corresponding to the second magnetostrictive peak in bulk samples. We quantify the amplitude of the induced magnetization oscillations using magnetic imaging in an x-ray photoelectron microscope and estimate the dynamic magnetoelastic constants through micromagnetic simulations. Our findings demonstrate the potential of galfenol thin films for magnonic applications and reveal that, despite strong magnetoelastic coupling, magnetic interactions and spin-wave dispersion relations significantly influence the overall amplitude of magnetoacoustic waves.